2017
DOI: 10.1063/1.5016778
|View full text |Cite
|
Sign up to set email alerts
|

Properties of polyamide 6-graphene-composites produced and processed on industrial scale

Abstract: Controlling the assembly of graphene based nanosheets within a rubber matrix: Nanocomposite morphology probed by measuring gas permeation and dielectric properties AIP Conference Proceedings 1736, 020066 (2016) Abstract. The use of graphene as a filler in thermoplastics has already been investigated extensively. The mechanical properties as well as electrical and thermal conductivity of thermoplastics can be improved due to graphene. However, these studies were carried out in experimental scale, which allows a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…Previous work on assessing the shore hardness of polymer composites reported slight increase which was attributed to the high surface area and dispersion of the reinforcement phase. [48][49][50] Incorporating GNPs in polymeric materials have been seen to lead to an increase 35,51,52 and reduction 45,[53][54][55] in tensile properties. Yesildag et al 52 reported a 20% increase in tensile modulus when 1 wt% GNPs was added to PA6.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work on assessing the shore hardness of polymer composites reported slight increase which was attributed to the high surface area and dispersion of the reinforcement phase. [48][49][50] Incorporating GNPs in polymeric materials have been seen to lead to an increase 35,51,52 and reduction 45,[53][54][55] in tensile properties. Yesildag et al 52 reported a 20% increase in tensile modulus when 1 wt% GNPs was added to PA6.…”
Section: Introductionmentioning
confidence: 99%
“…[48][49][50] Incorporating GNPs in polymeric materials have been seen to lead to an increase 35,51,52 and reduction 45,[53][54][55] in tensile properties. Yesildag et al 52 reported a 20% increase in tensile modulus when 1 wt% GNPs was added to PA6. The researchers claimed that further increase in graphene content does not significantly increase the modulus due to possible agglomeration.…”
Section: Introductionmentioning
confidence: 99%
“…There are various studies about the integration of graphene in polyamide matrix in the literature. For instance, Yesildag et al improved the Young's modulus up to 20% and tensile strength of the matrix up to 15% compared with neat PA6 by incorporating 1 wt% polar graphene into PA6 by using a co‐rotating intermeshing twin screw extruder but also stated that the Young's modulus did not increased with increasing graphene content due to the agglomeration of graphene 19 . Furthermore, Xu and Gao enhanced the tensile strength and Young's modulus of PA6 composites by 2.1 and 2.4 folds, respectively, by the addition of 0.1% graphene by in situ ring‐opening polymerization of PA6 20 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has shown high mechanical, thermal, and electrical properties. According to the report of Nafi Yesildag, et al, concerning the properties of polyamide 6-graphene composites, the Young's modulus and tensile strength were improved by the addition of 1 wt.% GP to PA, as compared to pure PA [56]. A study on the effect of graphene on crystallinity, electrical and thermal properties of polyamide 6 using melting compounding method was conducted by Hoor, Farzaneh Alirezaei, et al The results showed that the addition of graphene increased the thermal stability and electrical conductivity.…”
Section: Graphene/polyamide Composite Materialsmentioning
confidence: 99%